Impact of radiation on host immune system in patients treated with chemoradiotherapy and durvalumab consolidation for unresectable locally advanced non-small cell lung cancer - Corentin Pasquier; Léonor Chaltiel; Carole Massabeau; Audrey Rabeau; Louisiane Lebas; Amélie Lusque; Jean-Sébastien Texier; Elizabeth Cohen-Jonathan Moyal; Elizabeth Cohen-Jonathan Moyal; Elizabeth Cohen-Jonathan Moyal; Julien Mazières; Julien Mazières; et al. (Frontiers in Oncology, 2023)
BackgroundThe optimal modalities of radiotherapy when combining concurrent chemoradiation (CCRT) and immunotherapy (IO) for locally advanced non-small cell lung cancer (LA-NSCLC) remain to be determined. The aim of this study was to investigate the impact of radiation on different immune structures and immune cells in patients treated with CCRT followed by durvalumab.Material and methodsClinicopathologic data, pre- and post-treatment blood counts, and dosimetric data were collected in patients treated with CCRT and durvalumab consolidation for LA-NSCLC. Patients were divided into two groups according to the inclusion (NILN-R+) or not (NILN-R−) of at least one non-involved tumor-draining lymph node (NITDLN) in the clinical target volume (CTV). Progression-free survival (PFS) and overall survival (OS) were estimated by the Kaplan–Meier method.ResultsFifty patients were included with a median follow-up of 23.2 months (95% CI 18.3–35.2). Two-year PFS and 2-year OS were 52.2% (95% CI 35.8–66.3) and 66.2% (95% CI 46.5–80.1), respectively. In univariable analysis, NILN-R+ (hazard ratio (HR) 2.60, p = 0.028), estimated dose of radiation to immune cells (EDRIC) >6.3 Gy (HR 3.19, p = 0.049), and lymphopenia ≤ 500/mm3 at IO initiation (HR 2.69, p = 0.021) were correlated with poorer PFS; lymphopenia ≤ 500/mm3 was also associated with poorer OS (HR 3.46, p = 0.024). In multivariable analysis, NILN-R+ was the strongest factor associated with PFS (HR 3.15, p = 0.017).ConclusionThe inclusion of at least one NITDLN station within the CTV was an independent factor for poorer PFS in the context of CCRT and durvalumab for LA-NSCLC. The optimal sparing of immune structures might help in achieving better synergy between radiotherapy and immunotherapy in this indication.